If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(1 + 5n) = -1n + -13 (1 * 3 + 5n * 3) = -1n + -13 (3 + 15n) = -1n + -13 Reorder the terms: 3 + 15n = -13 + -1n Solving 3 + 15n = -13 + -1n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add 'n' to each side of the equation. 3 + 15n + n = -13 + -1n + n Combine like terms: 15n + n = 16n 3 + 16n = -13 + -1n + n Combine like terms: -1n + n = 0 3 + 16n = -13 + 0 3 + 16n = -13 Add '-3' to each side of the equation. 3 + -3 + 16n = -13 + -3 Combine like terms: 3 + -3 = 0 0 + 16n = -13 + -3 16n = -13 + -3 Combine like terms: -13 + -3 = -16 16n = -16 Divide each side by '16'. n = -1 Simplifying n = -1
| 10x-6x-2x=8 | | 4.5-1.4(6m+2)=6 | | 12+(-12)-(-5)= | | 5g-(8-g)=12 | | 4x-12x=64 | | 6[1-5x]-9=57 | | 12*0+3y=15 | | 1.8-.63x=.7(.3x+10.9) | | 2t+5t=56 | | 4x+4=9x+2 | | 3(s-4)=2(s-6) | | -4(-25)= | | 8x-3=4x-4 | | 9b+2=20 | | 5+4(-11+9)=-3 | | 27=3c-2(6-2c) | | -15(-4)(-1)= | | -.6+0.05z=5.3 | | x^2+3x-3x-4+x+x+3+4=51 | | -40-3= | | 8n-22=5n+5 | | 5[9-5n]-7=38 | | 9+g=-21 | | -(x+8)+2(x+8)=5-x+x-6 | | 5(-8)-3(-13)= | | 2(7n+8)-2(n+8)=4n+6n | | -6+0.05z=5.3 | | -5+y=23 | | 4x+6=2x+8 | | -9x=171 | | -6+0.05=5.3 | | x^3+2x^2=25x-50 |